Identification the Regularities of Influence of the Diesel Fuels Composition on the Efficiency of Low-Temperature Additives Action; Petroleum and Coal; Vol. 62, iss. 1 - Orlova A.; Bogdanov I. A. Ilya Aleksandrovich; Nikonova N. P. Njurguyaana Pavlovna; Kirgina M. V. Mariya Vladimirovna (2020, 2020)
Title screen